2019
DOI: 10.1186/s40425-019-0518-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of immune responses to anti-PD-1 mono and combination immunotherapy in hematopoietic humanized mice implanted with tumor xenografts

Abstract: BackgroundThe success of agents that reverse T-cell inhibitory signals, such as anti-PD-1/PD-L1 therapies, has reinvigorated cancer immunotherapy research. However, since only a minority of patients respond to single-agent therapies, methods to test the potential anti-tumor activity of rational combination therapies are still needed. Conventional murine xenograft models have been hampered by their immune-compromised status; thus, we developed a hematopoietic humanized mouse model, hu-CB-BRGS, and used it to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
150
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(165 citation statements)
references
References 53 publications
(58 reference statements)
15
150
0
Order By: Relevance
“…In contrast, the combined treatment of TTFields and anti-PD-1 did not result in changes in PD-L1 density in leukocytes from CT-26 tumors, and PD-L1 density was reduced in macrophages from tumors treated with TTFields monotherapy or the combination of the two modalities. This finding can be attributed to the long-term treatment duration in this model and is in line with a recent study by Capasso et al, showing that PD-L1 expression is increased in early stages of treatment with anti-PD-1 and is decreased in later stages [37]. It should also be noted that CT-26 cancer cells express high levels of PD-L1 on their surface while LLC-1 cancer cells do not express PD-L1; therefore, changes in PD-L1 expression in the tumor microenvironment can also potentially be affected by the PD-L1 expression by the cancer cells as well as by drug treatment schedule.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the combined treatment of TTFields and anti-PD-1 did not result in changes in PD-L1 density in leukocytes from CT-26 tumors, and PD-L1 density was reduced in macrophages from tumors treated with TTFields monotherapy or the combination of the two modalities. This finding can be attributed to the long-term treatment duration in this model and is in line with a recent study by Capasso et al, showing that PD-L1 expression is increased in early stages of treatment with anti-PD-1 and is decreased in later stages [37]. It should also be noted that CT-26 cancer cells express high levels of PD-L1 on their surface while LLC-1 cancer cells do not express PD-L1; therefore, changes in PD-L1 expression in the tumor microenvironment can also potentially be affected by the PD-L1 expression by the cancer cells as well as by drug treatment schedule.…”
Section: Discussionsupporting
confidence: 93%
“…To generate human immune system (HIS) mice, 0.2–0.6 × 10 6 expanded and thawed CD34+ cells were injected into neonate BRGS (BALB/c Rag2 nul l IL2Rγ null Sirpa NOD ) pups that had been irradiated with 300 rad 2–6 h prior to injection [ 18 ]. Mice were injected in the facial vein or liver, as previously described [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…To generate human immune system (HIS) mice, 0.2–0.6 × 10 6 expanded and thawed CD34+ cells were injected into neonate BRGS (BALB/c Rag2 nul l IL2Rγ null Sirpa NOD ) pups that had been irradiated with 300 rad 2–6 h prior to injection [ 18 ]. Mice were injected in the facial vein or liver, as previously described [ 18 ]. Mice were weaned at 3–4 weeks of age and analyzed for human chimerism at 10 and 16 weeks of age by staining of PBMCs, isolated from retro-orbital bleeds, to determine human (hCD45+), T (hCD3, hCD8, hCD5) and B (hCD20) cell chimerism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TME regulates the differentiation and activation of immune cells to reduce their ability to recognize and eliminate tumour cells. Immune cell therapies that more accurately target tumour cells while restoring normal immune cell populations within the TME, enhancing normal immune cell function and disrupting the protective effects of the abnormal immune cell networks have become a new anti‐tumour option 109 . As early as 1998, studies demonstrated that transplanting immune‐activated splenocytes into mice with breast cancer caused tumour shrinkage and conferred long‐term tumour‐free survival, suggesting that adoptive immune cells can be effective anti‐tumour therapeutics 110 .…”
Section: Targeting the Tme To Break Through The Fortress Of The Tumourmentioning
confidence: 99%